Effectiveness of Guideline‐Recommended Cholecystectomy to Prevent Recurrent Pancreatitis. (March 2017) - Kamal, Ayesha; Akhuemonkhan, Eboselume; Akshintala, Venkata S; Singh, Vikesh K; Kalloo, Anthony N; Hutfless, Susan M
Abstract : OBJECTIVES: Cholecystectomy during or within 4 weeks of hospitalization for acute biliary pancreatitis is recommended by guidelines. We examined adherence to the guidelines for incident mild‐to‐moderate acute biliary pancreatitis and the effectiveness of cholecystectomy to prevent recurrent episodes of pancreatitis. METHODS: Individuals in the 2010–2013 MarketScan Commercial Claims & Encounters database with a hospitalization associated with International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM) codes of 577.0 for acute pancreatitis and 574.x for gallstone disease were eligible. Guideline adherence was considered cholecystectomy within 30 days of the first/index hospitalization for biliary pancreatitis. Individuals with and without guideline‐adherent cholecystectomy were compared for subsequent hospitalization for acute or chronic pancreatitis using a Cox proportional hazards model adjusted for age, sex, comorbidities, and length of index hospital stay. RESULTS: Of the 17, 010 patients who met the inclusion criteria, 78% were adherent with the guidelines, including 10, 918 who underwent cholecystectomy during the index hospitalization and 2, 387 who underwent cholecystectomy within 30 days. Among 3, 705 patients non‐adherent with the guidelines, 1, 213 had a cholecystectomy 1–6 months after the index hospitalization. Guideline‐adherent cholecystectomy resulted in fewer subsequent hospitalizations for acute and chronic pancreatitis as compared with non‐adherence to the guidelines (acute pancreatitis: 3% vs. 13%, P <0.001; chronic pancreatitis: 1% vs. 4%, P <0.001). CONCLUSIONS: Nearly four out of five patients underwent cholecystectomy for acute biliary pancreatitis in a timeframe, consistent with guidelines. Adherence resulted in a decrease in subsequent hospitalizations for both acute and chronic pancreatitis. However, the majority of non‐adherent patients did not undergo a subsequent cholecystectomy. There may be factors that predict the need for immediate vs. delayed cholecystectomy.